THE ROLE OF NATIONAL SOCIAL STATES FOR PRESERVATION AND PROTECTION OF SOCIAL VALUES IN THE CONTEXT OF NEOLIBERAL GLOBAL ORDER - Domeniko Kvartuč; Valentino Kuzelj (Elektronički Zbornik Radova Veleučilišta u Šibeniku)
Globalization, as a process that strives for the universality and singularity of the world, raises the complex question of ways to confront economic inequalities as a consequence of the neoliberal model of world market integration. Bearing in mind the restructuring nature of this process, which takes place on several levels, it is concluded that the resulting relations in the world trade network diminish the importance of the financial sovereignty of national states. Given this, economic inequalities are perpetuated, and the social instruments of national states have been blocked due to networking in the global market that follows the pattern of the neoliberal paradigm. The paper presents the levels at which global market integration takes place (macro, meso, and micro), and highlights the various effects of the globalization process on developed (Western) democracies, emerging market economies, developing countries, and post-transition countries from socialism to democracy. In addition, the impact of economic processes, and crises on the constitutional order of national states is highlighted, which may result in “tacit” changes in the constitutional structures of individual states in the direction of dissolving the role of legislatures (as elected representatives of citizens) in creating economic, fiscal, and social policies. Finally, it is pointed out that, given the impossibility of unified regulation of the world market, mechanisms to combat the negative (social and economic) consequences of the globalization process need to be found within the framework of national states.